Role of oxidative stress and altered thyroid hormones in unexplained infertility - Rehana, R.; Hiba, I. R.; Mussarat, A.; Naheeha, T. I.; Lalani, S.*; Faiza, A. (PMA House in Karachi, Pakistan, 2020)
Objective: To explore the link between altered thyroid profile and oxidative stress marker in females with unexplained infertility. Methods: The cross-sectional case-control study was carried out at the Islamabad Clinic Serving Infertile Couples, Islamabad, Pakistan, from June 2016 to August 2017, and comprised women aged 18-40 years regardless of ethnic background who were divided into two groups; those with unexplained infertility were the cases, while fertile women acted as the controls. Serum was analysed for triiodothyronine, thyroxine and thyroid stimulating hormone as well as for oxidative stress markers including manganese superoxide dismutase, glutathione reductase and adrenaline using enzymelinked immunosorbent assay. Data was analysed using SPSS 19. Results: Of the 88 subjects, there were 44(50%) in each of the two groups. There was no significant difference in terms of thyroids markers except thyroxine and thyroid stimulating hormone (p<0.05). There were significant differences in terms of oxidative stress markers between the groups (p<0.05). A significant positive correlation of thyroid stimulating hormone was observed with manganese superoxide dismutase and adrenaline (p<0.05) with a weak non significant association of glutathione reductase (p>0.05). Conclusions: Increased thyroxine levels in females with unexplained infertility was associated with decrease in the serum levels of antioxidants.